MODEL KOPERASI PESANTREN DAN KEMANDIRIAN EKONOMI : STUDI KOPONTREN AL-IKHLAS MAGETAN JAWA TIMUR - Hamdani, Hamdani (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to examine the management of the Al-Ikhlas Islamic boarding school cooperative in Krakas, Magetan, East Java, in managing santri-based finances. This cooperative carries an inclusive model with the principle of